2006
DOI: 10.1111/j.1469-7610.2006.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Assessment and treatment of refugee children and adolescents who have experienced war‐related trauma

Abstract: More research is required in order to expand our limited knowledge base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
276
1
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(303 citation statements)
references
References 107 publications
9
276
1
17
Order By: Relevance
“…In their review article, Ehntholt and Yule (68) found that young refugees were frequently subjected to multiple traumatic events and severe losses, as well as ongoing stressors within the host country. Although young refugees are often resilient, many experience mental health difficulties, including PTSD, depression, anxiety and grief.…”
Section: Treatment or How To Help To War Traumatized Children And Adomentioning
confidence: 99%
“…In their review article, Ehntholt and Yule (68) found that young refugees were frequently subjected to multiple traumatic events and severe losses, as well as ongoing stressors within the host country. Although young refugees are often resilient, many experience mental health difficulties, including PTSD, depression, anxiety and grief.…”
Section: Treatment or How To Help To War Traumatized Children And Adomentioning
confidence: 99%
“…In addition, it is important to note that positive experiences of school belonging play a particularly important role for young refugee students not only because of the outcomes of school belonging outlined above, but also because trauma and mental health interventions for refugees are increasingly being administered through schools (Ehntholt & Yule, 2006). It is plausible to suggest that if levels of school belonging are not high, such interventions risk being less effective from the very beginning.…”
Section: School Belonging In Refugee Studentsmentioning
confidence: 99%
“…A large research body indicates that they shake the basic sense of security and give rise to posttraumatic symptoms among adults [18,19] and teens [20]. These symptoms include delayed emotional and behavioral problems [21], posttraumatic stress disorders (PTSD), and depression, anxiety and grief [18].…”
Section: Ratio (Svr)mentioning
confidence: 99%